Pesquisa de Trypanosoma cruzi em cães e triatomíneos em área rural do município de Mossoró, Rio Grande do Norte - Freitas, Yannara Barbosa Nogueira (Universidade Federal Rural do Semi-Árido, 2016)
Affecting humans and various animals and occurring predominantly in rural areas, Chagas disease (CD) is caused by the protozoan Trypanosoma cruzi and has dogs as the main reservoirs in the domestic cycle of the disease. Thus, it aimed to investigate the presence and T. cruzi infection in triatomine. And, in parallel, to seek dogs seropositive to T. cruzi antigens and analyze possible risk factors for infection in dogs. The survey was conducted in the rural area of the municipality of Mossoró, Northeast Brazil, in 11 propriedades with triatomine capture history. Was performed active entomological research and identification of insects and T. cruzi research using the techniques of isolation in culture and polymerase chain reaction (PCR). For the mapping of vectors was used Quantum GIS 2.8.3 software. Was performed serological diagnosis canine using enzyme-linked immunosorbent assay (ELISA) and indirect immunofluorescence (IIF). Was confirmed the presence of vectors in eight of the 11 property in the study. Were captured 68 insects, 25 nymphs and 43 adult insects identified as Triatoma brasiliensis brasiliensis, Triatoma pseudomaculata, Rhodnius nasutus and Panstrongilus lutzi. All examined specimens (51 specimens) were negative for T. cruzi infection by isolation technique in culture, and of these, 41.17% (21/51) were positive, specified by 90.48% (19/21) nymphs and 9 52% (2/21) T. b. brasiliensis. Eleven percent (25/218) of evaluated dogs were seropositive in both tests, but there was no association between seropositive dogs with the presence and T. cruzi infection in triatomine or factors such as gender, age, function, presence of shelter for dogs and contacts. The mapping identified the areas of greatest risk transmission of the parasite. Thus, it was confirmed the presence of CD vector species in the rural area of the municipality of Mossoro, highlighting the species T. b. brasiliensis as potential vector of the parasite in the region. Therefore, in the study area, the maintenance cycle of disease transmission vector is clear and possible, since there are vectors and reservoirs infected domestic in the home area, increasing the risk of transmission to humans
Keywords: Doença de Chagas; vigilância epidemiológica; vetor; reservatório doméstico; Chagas disease; epidemiological surveillance; vector; domestic reservoir; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE